Potential Competitiveness of Indonesian Rubber Export in International Trade - Fadhilah, Alfirah; Fariyanti, Anna; Adhi, Andriyono Kilat (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 19 No 2 (2025): Vol 19 No 2 (2025)DO - 10.24843/SOCA.2025.v19.i02.p03, 2025)
The demand for rubber continues to rise in countries with established automotive industries. However, the potential of Indonesia’s rubber as an export commodity, along with its domestic absorption, has not yet matched the opportunities available in the international rubber market. This discrepancy, reflected in the decline in both value and volume of Indonesian rubber exports over recent years, poses a threat if left unaddressed. This study aims to analyze the competitiveness of Indonesian rubber exports to destination countries and to examine Indonesia’s market position and export potential in those countries. The data utilized in this research consist of Indonesia’s rubber export values, which are analyzed using the Revealed Comparative Advantage (RCA), Export Product Dynamics (EPD), and the X-Model of Product Export Potential. The findings indicate that rubber is a commodity with a strong comparative advantage, supported by Indonesia’s natural endowments, affirming its role as a key rubber-exporting country in the global market. Furthermore, the development of rubber export markets in importing countries demonstrates promising potential.